Effectiveness of Preventive Measures in Keeping Low Prevalence of SARS-CoV-2 Infection in Health Care Workers in a Referral Children's Hospital in Southern Italy - Désirée Caselli; Daniela Loconsole; Rita Dario; Maria Chironna; Maurizio Aricò (MDPI AG, 2021)
The coronavirus disease 2019 (COVID-19) pandemic now represents a major threat to public health. Health care workers (HCW) are exposed to biological risk. Little is currently known about the risk of HCW operating in pediatric wards for SARS-CoV-2 infection. The aim is to assess the prevalence of SARS-CoV-2 infection in HCW in a third-level children's hospital in Southern Italy. An observational cohort study of all asymptomatic HCW (physician, technicians, nurses, and logistic and support operators) was conducted. HCW were screened, on a voluntary basis, for SARS-CoV-2 by RT-PCR on nasopharyngeal swab performed during the first wave of COVID-19. The study was then repeated, with the same modalities, at a 7-month interval, during the "second wave" of the COVID-19 pandemic. At the initial screening between 7 and 24 April 2020, 525 HCW were tested. None of them tested positive. At the repeated screening, conducted between 9 and 20 November 2020, 627 HCW were tested, including 61 additional ones resulting from COVID-emergency recruitment. At this second screening, eight subjects (1.3%) tested positive, thus being diagnosed as asymptomatic carriers of SARS-CoV-2. They were one physician, five nurses, and two HCW from the logistic/support services. They were employed in eight different wards/services. In all cases, the epidemiological investigation showed convincing evidence that the infection was acquired through social contacts. The study revealed a very low circulation of SARS-CoV-2 infection in HCW tested with RT-PCR. All the infections documented in the second wave of epidemic of SARS-CoV-2 were acquired outside of the workplace, confirming that in a pediatric hospital setting, HCW education, correct use of personal protective equipment, and separation of the COVID-patient pathway and staff flow may minimize the risk derived from occupational exposure.